Dampak Stigma Bahasa Terhadap Kepercayaan Diri Penutur Bahasa Arab - Luthfi, Muhammad Ilham; Setiyawan, Agung (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2024)
Language stigma against Arabic can create a challenging environment for speakers, which in turn can reduce their confidence in various aspects of daily life. This study aims to analyze the factors influencing low self-confidence in speaking Arabic in Indonesia, particularly among students, and to identify the negative stigma attached to Arabic language learning and its impact on motivation and participation in using Arabic. The research method employed is field research with a descriptive qualitative approach, where data was collected through direct observation and interviews with non-native Arabic-speaking university students. The findings reveal that stigma surrounding the Arabic language, such as the perception of Arabic as only a religious language, being considered an ancient and irrelevant language, and the difficulties in pronunciation and grammar, contribute to low self-confidence in speaking Arabic. The study also found that the general public’s lack of understanding of the importance of Arabic and the lack of support for Arabic education outside Islamic educational institutions exacerbates the issue. To address this stigma, the study recommends raising awareness about the significance of Arabic through positive media campaigns, encouraging the use of Arabic in various sectors, and creating a supportive environment for Arabic speakers to practice without the fear of judgment. These efforts are expected to improve the self-confidence of Arabic speakers and foster the development of speaking skills in Arabic in Indonesia